Using a Genetic Algorithm to Produce Slogans - Tomašič, Polona; Papa, Gregor; Žnidaršič, Martin (Informatica, 2015)
Creative tasks, such as creation of slogans for companies, products or similar entities, can be viewed from the combinatorial perspective – as a search through the space of possible combinations. To solve such a combinatorial optimization problem, we can use evolutionary algorithms. In this paper, we present our solution for generation of slogans based on a genetic algorithm and linguistic resources. We also compare it to the unguided slogan generator.